Vegetation patterns along micro-relief and vegetation type transects in polygonal landscapes of the Siberian Arctic - Zibulski, Romy; Herzschuh, Ulrike (Prof. Dr.); Pestryakova, Luidmila A. (Prof. Dr.) (Journal of Vegetation Science, 2016)
QuestionHow important is the effect of micro-relief and vegetation type on the characteristics of vascular plants and bryophytes in low-centred polygons? LocationSiberian Arctic, Russia. MethodsEight low-centred polygons in northern Siberia were surveyed for vegetation along transects running from the rim to the pond via the rim-pond transition of each polygon and across a vegetation type gradient from open forest to tundra. ResultsThe cover of vascular plants and bryophytes displays no significant differences between the rim and rim-pond transition but is significantly lower in the pond section of the polygons. Alpha-diversity of vascular plants decreases strongly from rim to pond, whereas bryophyte diversity in pond plots is significantly distinct from the rim and the rim-pond transition. There is no clear trend in cover for either plant group along the vegetation type transect and only a weak trend in -diversity. However, both gradients are reflected in the compositional turnover. The applied indicator species analysis identified taxa characteristic of certain environmental conditions. Among others, we found vascular plants primarily characteristic of the rim and bryophyte taxa characteristic of each micro-relief level and vegetation type. ConclusionsThe observed gradual pattern in -diversity and composition of polygonal vegetation suggests that micro-relief is the main driver of changes in the vegetation composition, while vegetation type and the related forest cover change are of subordinate importance for polygonal vegetation patterns along the Siberian tree line.